Interplay of protein corona and immune cells controls blood residency of liposomes - Francesca Giulimondi (Nature Portfolio, 2019)
Protein corona formation is known to have significant effects upon nanomaterials application. Here, the authors investigate the creation of a protein coating on liposomes with the aim of improving liposome circulation time by avoiding leukocyte capture and demonstrated application in vitro and ex vivo.